2002
DOI: 10.1046/j.1365-2591.2002.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of different types of sodium perborate used for intracoronal bleaching of discoloured teeth

Abstract: The data obtained from this study demonstrate that sodium perborate can be used mixed with water rather than with hydrogen peroxide for bleaching discoloured teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
12

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 10 publications
2
53
0
12
Order By: Relevance
“…After 14 days (Rotstein et al, 1991c) and one year (Rotstein et al, 1993), there was no difference in the shade of the teeth bleached with sodium perborate in 30% hydrogen peroxide, sodium perborate in 3% hydrogen peroxide, or sodium perborate in water. Concurring results were found in a study with sodium perborate mixed with 30% hydrogen peroxide or water and evaluated after 7, 14, and 21 days of treatment (Ari and Üngör, 2002). Increased lightening of the teeth was observed with longer bleaching time, but otherwise no difference was reported.…”
Section: (Iv-2) Efficacymentioning
confidence: 99%
“…After 14 days (Rotstein et al, 1991c) and one year (Rotstein et al, 1993), there was no difference in the shade of the teeth bleached with sodium perborate in 30% hydrogen peroxide, sodium perborate in 3% hydrogen peroxide, or sodium perborate in water. Concurring results were found in a study with sodium perborate mixed with 30% hydrogen peroxide or water and evaluated after 7, 14, and 21 days of treatment (Ari and Üngör, 2002). Increased lightening of the teeth was observed with longer bleaching time, but otherwise no difference was reported.…”
Section: (Iv-2) Efficacymentioning
confidence: 99%
“…29 In vitro studies have concluded that sodium perborate in water, sodium perborate in 3% and 30% hydrogen peroxide, and 10% carbamide peroxide are all efficient at internal bleaching of non-vital teeth. [30][31][32][33][34] Various heat sources may be applied to speed the reaction and improve the bleaching effect. 35 The medicament is sealed in the pulp chamber for three to seven days, and is thereafter replaced regularly until acceptable lightening is achieved.…”
Section: Chemical Reactions Of Hydrogen Peroxidementioning
confidence: 99%
“…Most reports have very low initial results after bleaching, with complete color matching of the bleached tooth with the adjacent one. 6 However, occasionally darkening after internal bleaching can be observed which is presumably caused by diffusion of staining substances and penetration of bacteria through marginal gaps between the filling and the tooth. 7 Some modifications have been done in an attempt to minimize the risk of cervical or apical resorption; thus, a base of 1 -2 mm glass ionomer cement was placed over filling material of the root to have a mechanical barrier between the sealed root canal and the bleaching gel, which is in agreement with other studies Friedman et al as they did not use an intermediate lining prior to the bleaching material.…”
Section: Discussionmentioning
confidence: 99%